2020
DOI: 10.1126/sciadv.aaz5216
|View full text |Cite
|
Sign up to set email alerts
|

The origin of domestication genes in goats

Abstract: Goat domestication was critical for agriculture and civilization, but its underlying genetic changes and selection regimes remain unclear. Here, we analyze the genomes of worldwide domestic goats, wild caprid species, and historical remains, providing evidence of an ancient introgression event from a West Caucasian tur-like species to the ancestor of domestic goats. One introgressed locus with a strong signature of selection harbors the MUC6 gene, which encodes a gastrointestinally secreted mucin. Experiments … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
100
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 115 publications
14
100
0
Order By: Relevance
“…OL and BZ showed a strong correlation since 100,000 years ago. At 20,000 years, the effective population size of TST increased 65 , 66 .
Figure 3 Demographic history of the sheep populations.
…”
Section: Resultsmentioning
confidence: 99%
“…OL and BZ showed a strong correlation since 100,000 years ago. At 20,000 years, the effective population size of TST increased 65 , 66 .
Figure 3 Demographic history of the sheep populations.
…”
Section: Resultsmentioning
confidence: 99%
“…S11). Thus, the east-west distinction between goat populations emerges early, likely reflecting the differentiating effects of separate inputs from regional wild populations (10,37).…”
Section: An Zagros Goat Form Distinct Wild-affinity and Domestic-affinity Clustersmentioning
confidence: 99%
“…In this model, Zagros Outlier is an outgroup to other Iranian Neolithic genomes, including those from East Iran/ Turkmenistan and the Zagros Main group. Goat from Neolithic Serbia also receive a majority (∼70%) of their ancestry from this clade after their divergence from Zagros Outlier, but derive additional ancestry related to both Epipaleolithic Turkish wild goat (∼30%) and the Caucasian Tur Capra caucasica (∼1%) (10,37). In contrast, the Zagros Main and later East Iranian/Turkmeni Neolithic goat populations-separated by ∼1,800 y and ∼680 km-are modeled as differentiated by drift alone rather than by introgressing wild ancestry, a result supported by qpWave modeling using modern wild goats (SI Appendix, Table S15), although D statistics do not rule out differential wild affinities among Neolithic Iranian goat (SI Appendix, Fig.…”
Section: Zagros Outliermentioning
confidence: 99%
“…In another study, the analysis of wild caprids and whole genomes of domestic goats revealed ancient introgression evidence from a West Caucasian tur-like population to the ancestor of domestic goats. It was further revealed that the MUC6 gene was an introgression locus with a strong selection signature and conferred enhanced immune resistance to gastrointestinal pathogens ( Zheng et al, 2020 ). The third case is the wild yeast ( Saccharomyces eubayanus ).…”
Section: Discussionmentioning
confidence: 99%